Investigação sobre a dor em idosos submetidos a tratamento fisioterapêutico - Freire, Regina Célia Torres (2007)
Due to the fact that ageing will increase in the next decades, the demand for health service and the need for a basic infrastructure of care and support, the main purpose of this master thesis is to study and thoroughly understand better the relationship between pain and ageing. This research is based on a general idea that pain is an inherent process of ageing. This thesis deals with this question in a multidimensional context, using a broader approach, and seeks to clarify the relationship between ageing and pain studying how elderly people under physiotherapic treatment perceive pain. We proceeded a qualitative research based on interviews and the results were here presented on a descriptive way, with illustrative quotations. The data analysis revealed that most of elderly people think pain comes concomitantly along with ageing, having a direct effect in their lives and decreasing their independence. They see pain as something that turns their day-by-day activities harder. For elderly people, pain and illness are synonyms and they use to relate pain to ageing. In their minds, pain threats their quality of life and their plans for the future. They believe that physioterapy could help them to reduce their suffering, but they have problems in finding proper treatment. On the other hand, when they start physioterapic sessions they are afraid of what will happen if the treatment is interrupted. This research revealed that we need to rethink the ways how physioterapic treatment has been applied until now; we should move our focus from the illness to the individuals. Our research concluded that it is necessary a better training to the professional involved with old age, and that we have to improve the support network to elderly people